B-108 Specific HIV integration sites are linked to clonal expansion and persistence of infected cells. (January 2016) - Maldarelli, Frank; Wu, Xiaolin; Su, Ling; Simonetti, Francesco; Wells, David; Shao, Wei; Spindler, Jonathan; Ferris, Andrea; Mellors, John; Kearney, Mary; Coffin, John; Hughes, Stephen
Abstract : HIV integrates its DNA into many sites in the host genome; thus integration sites can be used as markers to identify clonally expanded cells. We identified the integration sites in PBMCs and CD4+ T cells from patients and used these data to show that there is extensive clonal expansion of infected cells. We have started to determine the sequences of viral DNAs in clonally expanded cells; these sequences are being used to study the structure and expression of the proviruses present in expanded cells. We have identified >2500 integration sites in PBMCs and CD4+ cells from infected individuals on combination anti-retroviral therapy (cART). About 40% of the integrations were in clonally expanded cells. In one patient, more than 50% of the infected cells were from a single clone; some of the expanded clones persisted for more than 10 years. There were multiple independent integrations in the same orientation as the gene in 2 introns of the MKL2 and BACH2 genes; many of these integrations were in clonally expanded cells. Both BACH2 and MKL2 are involved in regulating the growth of cells. DNA rearrangements involving these genes have been found in human tumors. There was no evidence for integration in one orientation, or in specific introns, in either of these genes in large libraries prepared by infecting stimulated or unstimulated PBMCs, CD34+ cells, or HeLa cells that were infected in culture. There were, in patients, multiple independent integrations in a number of other growth related genes, some of which were associated with clonal expansion of the infected cells. These data show that HIV integration at certain sites can play a critical role in the expansion and persistence of HIV infected cells. In one case, we showed that the provirus in an expanded clone was responsible for producing the majority of the virus that was present in the blood of a patient on cART, showing that, in this patient, immune surveillance was not sufficient to prevent clonally expanded cells from producing virions. Additional experiments showed that this virus is replication competent, demonstrating that clonally expanded cells can carry replication competent proviruses that produce infectious virus in patients. Thus, proviruses in clonally expanded cells can be part of the reservoir that gives rise to replicating virus when therapy is interrupted. Our findings have important implications for the development and maintenance of the viral reservoir, for designing and implementing strategies to eliminate persistent HIV infection, for the use of lentiviral vectors for gene therapy in human patients, and, possibly, for the origin of some HIV-related malignancies.